TIMBULAN LEACHATE DARI LANDFILL LYSIMETER DENGAN LAPISAN PENUTUP BERBAHAN DASAR LIMBAH ABU SEKAM PADI - Mizwar, Andy (Bumi Lestari; Vol 15 No 1 (2015))
The purpose of this study was to determine the effect of the use of rice husk ash as a landfill cover on the quantity and characteristics of leachate generated from landfill lysimeter. Three lysimeters with diameter and height of 0,15 and 2 m, respectively, were prepared. Two lysimeters were filled with municipal waste and two different cover types i.e. soil (lysimeter A) and rice husk ash (lysimeter B) while another lysimeter was filled solely with municipal waste (lysimeter C). Leachate quantities and characteristics were measured and determined once a week. The cumulative leachate quantity from the lysimeter B was found to 69,33% and 43,93% less than the lysimeter C and A respectively. There were no any differences of the pH value of the leachate generated from all lysimeters. The comparison of the leachate characteristics showed that the lysimeter B generate the TSS concentrations 45,95% and 52,93% less than the lysimeter C and A respectively, however the TDS concentrations were 130,73% and 60,91% more than lysimeter C and A respectively. In addition, the use of rice husk ash as a landfill cover could reduce ± 85% of organic matter in the leachate generated.
Keywords: landfill cover, leachate, lysimeter, rice husk ash